A yeast shadow-based core-shell structure superparamagnetic gold-doped iron-based composite nanoscale enzyme and a preparation method and application thereof

CN122895007APending Publication Date: 2026-10-13HENAN AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611028875.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,传统纳米酶存在活性位点密度低、分布随机、结构复杂、催化选择性差等问题,难以达到天然酶的高效性与特异性

Benefits of technology

[0016]本发明相对现有技术具有突出的实质性特点和显著进步,具体的说,本发明提供一种基于酵母菌影的核壳结构超顺磁性金掺杂铁基复合纳米酶。酵母活化后,经甲醛固定、酸碱处理得到多孔空壳的酵母菌影,以酵母菌影为载体,原位组装胶体金与Fe-MOF后高温煅烧,成功合成了Au-FeSAzyme纳米酶。该纳米酶具有优异的类过氧化物酶活性,比酶活为2.17 U/mg,且亚硝酸盐对其活性呈浓度依赖性抑制。稳态动力学分析表明,Au-FeSAzyme对H2O2的Km值为0.242 mM,显著低于天然辣根过氧化物酶(3.700 mM),且对TMB的Vm更高,展现出更强的底物亲和力与催化效率。基于亚硝酸盐特异性抑制显色反应的原理,构建了比色检测体系:在0.1–20 mM线性范围内,652 nm吸光度与亚硝酸盐浓度呈良好线性关系(R2>0.99),检测限为0.01 mM。实际样品加标回收率为96.32%-108.51%,证明该方法准确可靠,且具有良好的抗干扰能力。该检测方法操作简便、成本低、灵敏度高,为食品安全中亚硝酸盐检测提供了高效实用的新策略,具有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895007A_ABST
    Figure CN122895007A_ABST
Patent Text Reader

Abstract

The application provides a kind of based on yeast ghost's core-shell structure superparamagnetic gold-doped iron-based composite nanozyme, the composite nanozyme is obtained by mixing yeast ghost, chloroauric acid solution, ascorbic acid solution reaction, and yeast ghost structure is contained in yeast ghost@AuNPs complex;Yeast ghost@AuNPs complex is mixed uniformly in ferrous ion solution, then benzenetricarboxylate solution is added to fully react, and then centrifugal collection is carried out in sequence to obtain yeast ghost@AuNPs@Fe-MOF complex, and then the complex is used to adsorb hemin to obtain yeast ghost@AuNPs@Fe-MOF@hemin, which is dried and calcined to obtain the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of detection, specifically to a core-shell structured superparamagnetic gold-doped iron-based composite nanozyme based on yeast shadow, its preparation method, and its application in the detection of nitrite in food. Background Technology

[0002] Nitrite (NO) 2- Nitrites are widely present in the environment and food, and are important food additives. They can inhibit the growth of microorganisms, especially pathogenic bacteria such as Clostridium botulinum and spoilage bacteria, thus extending the shelf life of meat products. They can also react with myoglobin to form nitrosomyoglobin, giving meat products a bright rose-red color and enhancing flavor. my country's national standards stipulate that the residual amount of nitrite in food should be ≤ 30 mg / kg. Nitrites in food pose serious health risks, but existing detection methods, such as spectrophotometry and chromatography, are limited by complex equipment and high costs. Therefore, developing a rapid and accurate method for detecting residual nitrite has significant practical significance and application value.

[0003] Nanozymes are a class of functionalized nanomaterials with catalytic properties similar to natural enzymes. They exhibit catalytic performance by mimicking the active site structure of natural enzymes such as peroxidase (POD), oxidase (OXD), and catalase (CAT). Compared with natural enzymes, nanozymes have outstanding advantages such as high environmental stability, low production cost, strong catalytic activity, simple synthesis, easily tunable activity, high substrate affinity, and immunity to biodegradation. In 2007, Yan Xiyun's team formally proposed the concept of "nanozymes," overturning the traditional understanding of enzymology as being dependent on proteins. Since then, various nanomaterials such as gold, copper, and carbon-based nanomaterials have been found to possess enzyme-like activities such as oxidase and catalase, and have been widely used in fields such as biosensing, antibacterial therapy, and environmental pollution control. However, traditional nanozymes suffer from problems such as low active site density, random distribution, complex structure, and poor catalytic selectivity, making it difficult to achieve the high efficiency and specificity of natural enzymes.

[0004] In order to solve the above problems, people have been seeking an ideal technological solution. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a core-shell structured superparamagnetic gold-doped iron-based composite nanozyme based on yeast shadows, its preparation method, and its application in the detection of nitrite in food.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a yeast shadow-based core-shell structured superparamagnetic gold-doped iron-based composite nanozyme includes the following steps: mixing yeast shadow, chloroauric acid solution, and ascorbic acid solution to obtain a yeast shadow-containing complex (yeast ghost@AuNPs); mixing the yeast ghost@AuNPs complex with a ferrous ion solution, then adding a benzotrimethylammonium salt solution and reacting thoroughly; centrifuging and collecting the precipitate to obtain a yeast ghost@AuNPs@Fe-MOF complex; then using this complex to adsorb heme chloride to obtain yeast ghost@AuNPs@Fe-MOF@hemin; and finally drying and calcining to obtain the final product. Because heme chloride contains iron and its unique molecular structure results in a specific spatial distribution of iron atoms, the adsorption of heme chloride by the complex further increases the iron content in the composite material, resulting in the calcined yeast shadow-based core-shell structured superparamagnetic gold-doped iron-based composite nanozyme (Au-FeSAzym) exhibiting higher peroxidase-like activity.

[0007] First, add chloroauric acid solution to the yeast culture and react for 1-3 hours, then add ascorbic acid solution for 15-50 minutes to obtain chloroauric acid solution.

[0008] Dry yeast was sequentially activated, fixed with formaldehyde, and treated with acid and alkali to obtain yeast cells. Specifically, fixation was performed using 10% formaldehyde solution at 4℃ for 4-12 h, followed by fixation using NaOH solution (100 mmol / L NaOH, 80℃, 1 h) and dilute hydrochloric acid solution (pH 4.5, 55℃, 1 h).

[0009] The benzotricarboxylate solution is prepared by dissolving 1,3,5-benzotricarboxylic acid in an alkaline solution; the pH value of the benzotricarboxylate solution is 10.5-11.5, and the alkaline solution is potassium hydroxide or sodium hydroxide solution.

[0010] Ferrous ion solution is prepared by dissolving divalent ferrous salt in deionized water, and the pH value of ferrous ion solution is 2-3.

[0011] The molar ratio of chloroauric acid, 1,3,5-benzenetricarboxylic acid and divalent ferrous salt is (0.01-0.06):(1-2):(1-5).

[0012] The complex adsorbs heme chloride for 1-4 h to obtain yeast ghost@AuNPs@Fe-MOF@hemin; then it is calcined at 400-750℃ for 1-4 h to obtain the composite nanozyme.

[0013] A superparamagnetic gold-doped iron-based composite nanozyme with a core-shell structure based on yeast shadow was prepared by the above-described method.

[0014] A method for applying the yeast shadow-based core-shell structured superparamagnetic gold-doped iron-based composite nanozyme in the detection of nitrite in food includes the following steps: homogenizing the food sample to be tested, extracting the supernatant and filtering it; mixing the sample supernatant, composite nanozyme aqueous solution, TMB solution, H2O2 solution and acetate buffer solution evenly to obtain a reaction system; reacting the reaction system and measuring the absorbance at 652 nm using an enzyme-linked immunosorbent assay (ELISA) reader; substituting the measured absorbance into a pre-plotted standard curve to calculate the nitrite content in the sample to be tested.

[0015] The concentration of the composite nanozyme aqueous solution was 0.8 mg / mL, the amount of TMB and H2O2 used were 20 mM and 6 μL, respectively, and the pH of the reaction system was 3.5.

[0016] This invention represents a significant advancement over existing technologies, specifically providing a core-shell structured superparamagnetic gold-doped iron-based composite nanozyme based on yeast shadows. After yeast activation, the yeast shadows were fixed in formaldehyde and subjected to acid-base treatment to obtain porous, hollow-shell yeast shadows. Using these shadows as a carrier, colloidal gold and Fe-MOF were assembled in situ, followed by high-temperature calcination, successfully synthesizing Au-FeSAzyme nanozymes. These nanozymes exhibit excellent peroxidase-like activity, with a specific enzyme activity of 2.17 U / mg, and nitrite exhibits concentration-dependent inhibition of their activity. Steady-state kinetic analysis shows that Au-FeSAzyme has a Km value of 0.242 mM for H₂O₂, significantly lower than that of natural horseradish peroxidase (3.700 mM), and a higher Vm value for TMB, demonstrating stronger substrate affinity and catalytic efficiency. Based on the principle that nitrite specifically inhibits colorimetric reactions, a colorimetric detection system was constructed: within a linear range of 0.1–20 mM, the absorbance at 652 nm showed a good linear relationship with the nitrite concentration (R0). 2 The detection limit is 0.01 mM (>0.99). The actual sample spiked recoveries ranged from 96.32% to 108.51%, demonstrating the accuracy and reliability of the method and its good anti-interference ability. This detection method is simple to operate, low in cost, and highly sensitive, providing an efficient and practical new strategy for nitrite detection in food safety, and has broad application prospects. Attached Figure Description

[0017] Figure 1 Physicochemical properties analysis of Au-FeSAzyme. (a) SEM image of yeast; (b) SEM image of Au-FeSAzyme; (cf) Energy dispersive spectroscopy (EDS) images of (c) carbon, (d) oxygen, (e) iron, and (f) gold on the surface of Au-FeSAzyme particles.

[0018] Figure 2The image shows the X-ray diffraction pattern of Au-FeSAzyme.

[0019] Figure 3 The hysteresis loop parameters are used to characterize Au-FeSAzyme.

[0020] Figure 4 The following are the specific surface area and pore size distribution diagrams of yeast shadow and Au-FeSAzyme. (a) Specific surface area diagram of yeast shadow obtained after acid-base treatment; (b) Specific surface area diagram of yeast shadow obtained after acid-base treatment; (c) Specific surface area diagram of Au-FeSAzyme; (d) Pore size distribution diagram of Au-FeSAzyme.

[0021] Figure 5 Peroxidase-like (POD) activity and kinetic analysis of Au-FeSAzyme nanozymes. Reaction kinetic curves were monitored at 652 nm for 300 seconds (a) and 60 seconds (b) at different nanozyme concentrations; (cd) the specific activity (SA) of the nanozyme as a function of nitrite concentration; steady-state kinetic curves at different concentrations of H2O2 (e) and TMB (g); and Lineweaver-Burk double reciprocal plots were generated based on the H2O2 (f) and TMB (h) kinetic data.

[0022] Figure 6 Optimization of catalytic conditions for Au-FeSAzyme. (a) Effect of Au-FeSAzyme nanozyme concentration on the reaction system; (b) Effect of TMB concentration on the reaction system; (c) Effect of H2O2 dosage on the system; (d) Effect of pH on the system.

[0023] Figure 7 To detect nitrite based on Au-FeSAzyme colorimetric method. (a) UV-Vis absorption spectra of oxTMB in the presence of different concentrations of nitrite; (b) Standard curve of absorbance at 652 nm as a function of nitrite concentration (0.1–20 mM); (c) Standard curve of nitrite concentration versus RGB (B channel) value.

[0024] Figure 8 The recycling efficiency of Au-FeSAzyme nanozyme in the colorimetric detection of 10 mM nitrite was calculated. After each detection, the nanozyme was recovered by simple magnetic separation and reused, for a total of 3 cycles.

[0025] Figure 9 The effects of various variables on absorbance at 652 nm are shown. (a) Effect of different cations on absorbance at 652 nm (b) Effect of different anions on absorbance at 652 nm (c) Effect of different organic compounds on absorbance at 652 nm. Detailed Implementation

[0026] The technical solution of the present invention will be further described in detail below through specific embodiments. Example 1

[0027] This embodiment provides a core-shell structured gold-doped iron-based composite nanozyme based on yeast shadows, which is prepared through the following steps: After activation, dried yeast was fixed with 10% formaldehyde solution at 4℃ for 8 h, and then treated with alkali (100 mmol / L NaOH, 80℃, 1 h) and dilute hydrochloric acid (pH 4.5, 55℃, 1 h) to obtain yeast shadows. 1 g of yeast shadow was taken and reacted with 2 mL of 1% HAuCl4 for 2 h, followed by reduction with 2 mL of 5% ascorbic acid for 30 min to obtain a yeast ghost@AuNPs complex containing the yeast shadow structure. Preparation of Solution 1 (pH≈11): Accurately weigh 1,3,5-benzenetricarboxylic acid (H3BTC, 0.3352 g, 1.52 mmol) and dissolve it in 5 mL of 1 mol / L NaOH solution for later use; Prepare solution 2 (pH≈2.7): Accurately weigh ferrous chloride tetrahydrate (FeCl2⋅4H2O, 0.452 g, 2.27 mmol) and dissolve it in 20 mL of H2O for later use; The yeast ghost@AuNPs complex containing the yeast shadow structure was added to solution 2 and mixed thoroughly. Then, it was added dropwise to solution 1 and placed at 25 °C for 24 h. After centrifugation, the precipitate was collected to obtain the yeast ghost@AuNPs@Fe-MOF complex. Then, 25 mg of heme chloride was added for adsorption for 2 h to obtain yeast ghost@AuNPs@Fe-MOF@hemin. After drying, it was calcined at 500 °C for 2 h to obtain colloidal gold-doped iron single-atom nanozyme (Au-FeSAzyme). Example 2

[0028] This embodiment characterizes the Au-FeSAzyme prepared in Example 1: To observe the morphology of Au-FeSAzyme nanozymes, the nanomaterials were first placed in a 2 mL centrifuge tube containing anhydrous ethanol and sonicated for 10 min to ensure uniform dispersion. Then, 10 μL was dropped onto the matte surface of aluminum foil, dried in an oven, and stored in a clean centrifuge tube. The surface structure and structural details of the nanomaterials were then observed under a scanning electron microscope. To observe and analyze the elemental composition and distribution characteristics of the Au-FeSAzyme nanozymes, energy-dispersive spectroscopy (EDS) elemental mapping was performed on the prepared samples to characterize the distribution of carbon, oxygen, iron, and gold elements on the material surface. The test results are shown below. Figure 1 .

[0029] See Figure 1 , Figure 1 In Figure a, the yeast shadow is a morphological image. The yeast shadow retains its complete morphology after formaldehyde fixation and acid-base treatment. Figure 1 Image b shows the morphology of Au-FeSAzyme nanozyme, which is the result of in-situ assembly of colloidal gold and Fe-MOF followed by calcination. Figure 1 The cf in the figure represents the elemental mapping results, which show that the four elements C, O, Fe, and Au are uniformly distributed on the surface of the Au-FeSAzyme material, with no obvious elemental agglomeration or local enrichment. This indicates that the Au-FeSAzyme prepared by this method achieves uniform doping and effective loading of iron and gold active components on the carrier surface, and the material has excellent elemental dispersion.

[0030] To characterize the crystal structure diffraction peaks of Au-FeSAzyme nanozymes, Au-FeSAzyme nanozymes were placed in the sample chamber of an X-ray diffraction (XRD) spectra for scanning. The crystal type and lattice parameters of the material were characterized using a scan rate of 1° / min (λ=1.54056) and a scan range of 5–50°. The test results are shown below. Figure 2 .

[0031] See Figure 2 The Au-FeSAzyme nanoparticles synthesized in this invention exhibit sharp X-ray diffraction peaks at positions such as 7.5°, 12.5°, and 45°, indicating that the Au-FeSAzyme nanoparticles have formed a new crystal structure.

[0032] To characterize the hysteresis loop parameters of Au-FeSAzyme, approximately 20 mg of Au-FeSAzyme was packaged in a centrifuge tube, and the hysteresis loop was measured using a vibrating sample magnetometer (LakeShore 8600). The hysteresis loop characterization results are as follows: Figure 3As shown, Au-FeSAzyme is clearly a soft magnetic material with superparamagnetic properties. Au-FeSAzyme exhibits typical superparamagnetic characteristics at room temperature. Its saturation magnetization (Ms) is 30 emu / g, which meets the requirements for routine bioseparation. VSM (vibrating sample magnetometer) test results show that its hysteresis loop passes through zero, its coercivity (Hc) is zero, and its remanence (Mr) is zero, indicating that the material has no hysteresis loss and exhibits good monodispersity in aqueous solution without remanent agglomeration.

[0033] To accurately analyze the porous structure and microscopic pore parameters of Au-FeSAzyme nanozymes, nitrogen adsorption-desorption tests were performed on the Au-FeSAzyme nanozyme material to precisely characterize its specific surface area, average pore size, and pore volume parameters. The test results are shown below. Figure 4 .Depend on Figure 4 As shown in section ab, the specific surface area of ​​the yeast cells obtained after acid-base treatment is 0.87 m² / g, the average pore size is 27.9 nm, and the pore volume is 0.0011 cm³ / g. Figure 4 The results show that the Au-FeSAzyme nanozyme has a specific surface area of ​​541.8 m² / g, an average pore size of 9.2 nm, and a pore volume of 0.33 cm³ / g, representing increases of 623 times and 300 times in surface area and pore volume, respectively. Therefore, the prepared Au-FeSAzyme nanozyme possesses a high specific surface area and a typical mesoporous structure, providing ample catalytic active sites and diffusion channels. Combined with the uniform elemental doping characteristics of the material, this further confirms that this method can successfully prepare Au-FeSAzyme nanozyme materials with excellent structure and controllable performance. Example 3

[0034] This embodiment analyzes the enzyme activity of the Au-FeSAzyme nanozyme prepared in Example 1.

[0035] (1) Effects of different concentrations of nitrite on enzyme activity A certain amount of sodium nitrite solid was weighed and prepared with ultrapure water to obtain concentrations of 5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 mg / mL. Then, 74 μL of acetate buffer (0.2 M, pH=3.5), 10 μL of Au-FeSAzyme nanozyme aqueous solution (0.2 mg / mL), 1 μL of TMB solution (20 mM), 10 μL of sodium nitrite solutions of different concentrations, and 5 μL of 30% H2O2 solution were added sequentially. After mixing thoroughly by pipetting, the OD was measured using a multi-functional microplate reader. 652 nm Measure once every 10 seconds, for a total of 300 seconds.

[0036] Based on the measured OD 652 nmPlot a line graph with time on the x-axis and y-axis on the y-axis (see...). Figure 5 (a, c). Take the OD measured in the first 60 seconds. 652 nm Plot a scatter plot with time on the x-axis and fit a linear relationship (see...). Figure 5 (b) Using the measured OD 652 nm Substituting into the formula B = 100 / (39000 × 0.15) × ΔA yields the enzyme activity B, and substituting into SA = B / mAu-Fe yields the specific enzyme activity, where mAu-Fe represents the mass of the Au-FeSAzyme nanozyme, and ΔA represents the OD. 652 nm A bar chart was created with enzyme activity on the ordinate and sodium nitrite concentration on the x-axis (see [link]). Figure 5 (d).

[0037] like Figure 5 As shown in Figure ab, the Au-FeSAzyme nanozyme exhibits peroxidase (POD) activity, with a specific enzyme activity of 2.17 U / mg. Upon addition of nitrite, its POD specific enzyme activity decreases with increasing nitrite concentration. Figure 5 The presence of cd indicates that nitrite inhibits the POD activity of this nanozyme in a concentration-dependent manner.

[0038] (2) Using TMB as a substrate, the enzyme activity of Au-FeSAzyme nanozyme was analyzed.

[0039] To prepare 20 mM TMB, add 150 μL of acetate buffer (pH=3.5, 0.2 M), 5 μL of Lu-FeSAzyme nanozyme (0.8 mg / mL), and 6 μL of 30% hydrogen peroxide sequentially to an EP tube. Then add 0, 1, 2, 4, 6, 8, 10, and 15 μL of TMB solution sequentially, and balance the volume with buffer solution to a total volume of 200 μL. Measure the OD using a multi-functional microplate reader. 652 nm Measurements were taken every 10 seconds for a total of 300 seconds, and then the measured OD values ​​were used as the basis for the analysis. 652 nm Plot a scatter plot with time on the x-axis and the final TMB concentration on the x-axis, fit a linear relationship, and calculate the slope as the initial velocity V0. Use Origin to perform nonlinear fitting with the Enzyme Kinetics-Michaelismenten equation (see [link to Origin]). Figure 5 (e), calculate Vm and Km A linear relationship was fitted by taking the reciprocal of TMB concentration and initial reaction rate (see...). Figure 5 (f)

[0040] (3) Enzyme activity analysis of Au-FeSAzyme nanozyme was performed using H2O2 as a substrate. 0, 1, 2, 4, 6, 8, 10, and 15 μL of 30% H2O2 solution were added to groups 1-8, respectively. 5 μL of Au-FeSAzyme nanozyme (0.8 mg / mL) and 5 μL of LTMB solution were added to each group, and the total volume was balanced with acetate buffer (0.2 M, pH=3.5) to a total volume of 200 μL. OD was measured every 10 s. 652 nm The measurement lasted for 300 seconds, and then the measured OD was used as the basis for the result. 652 nm Plot a scatter plot with time on the x-axis and the final H₂O₂ concentration on the x-axis and the initial reaction velocity on the y-axis. Fit a linear relationship and calculate the slope as the initial velocity V₀. Use Origin for nonlinear fitting with the Enzyme Kinetics-Michaelismenten equation (see [link to Origin]). Figure 5 (g), calculate Vm and Km By taking the reciprocal of the H2O2 concentration and the initial reaction rate, a linear relationship was fitted (see...). Figure 5 (h).

[0041] like Figure 5 As shown in Figure 1, the Au-FeSAzyme-catalyzed reaction of H₂O₂ and TMB conforms to the Michaelis-Menten kinetic model. The measured kinetic parameters are: for H₂O₂, Km = 0.242 mM, Vm = 4.59 × 10⁻ 7 M·s⁻¹; for TMB, Km = 0.547 mM, Vm = 9.11 × 10⁻ 7 M·s⁻¹. With natural HRP ( Km Compared to H2O2 (3.700 mM), Au-FeSAzyme exhibits a higher affinity for H2O2 and is more effective with both substrates. V m Both were significantly greater than HRP, indicating that they can effectively promote TMB oxidation. Example 4

[0042] This embodiment optimizes the detection reaction conditions for the Au-FeSAzyme nanozyme prepared in Example 1.

[0043] 1. Concentration of Au-FeSAzyme nanozyme The concentration gradient of Au-FeSAzyme nanozyme was set at 0, 0.1, 0.4, 0.8, 1.6, 3.2, 6.4, and 12.8 mg / mL, with three replicates for each group. Each group contained 30 μL of sodium nitrite solution (1 mM), 30 μL of Au-FeSAzyme aqueous solution, 18 μL of 30% hydrogen peroxide solution, 30 μL of TMB (20 mM) solution, and 492 μL of acetate buffer (pH=3.5, 0.2 M). The reaction system was placed in a constant temperature shaker (30 ℃, 200 rpm) for 10 min, followed by centrifugation for 2 min (10000 rpm). 100 μL of the supernatant was diluted 4-fold and mixed thoroughly. 100 μL of this supernatant was then transferred to an ELISA plate, and the OD was measured using a multi-functional ELISA reader. 652 nm .

[0044] The results are as follows Figure 6 As shown in Figure a, when the concentration of Au-FeSAzyme nanozyme is between 0.1 and 0.8 mg / mL, the OD increases with increasing material concentration. 652 nm The concentration continuously increases; when the concentration is between 0.8-12.8 mg / mL, the OD increases with increasing material concentration. 652 nm The concentration of nanozyme continuously decreased. This indicates that the signal was most pronounced at a concentration of 0.8 mg / mL. Therefore, the optimal nanozyme concentration for this detection system was determined to be 0.8 mg / mL.

[0045] 2. TMB concentration TMB concentrations of 0, 5, 10, 20, 40, 60, 80, and 100 mM were set up, with three replicates for each group. Each group contained 30 μL of sodium nitrite solution (1 mM), 18 μL of 30% hydrogen peroxide solution, 30 μL of Au-FeSAzyme nanozyme solution (0.8 mg / mL), 30 μL of TMB solution, and 492 μL of acetate buffer (pH=3.5, 0.2 M). The reaction mixture was placed in a constant temperature shaker (37 ℃, 200 rpm) for 10 min, followed by centrifugation for 2 min (12000 rpm). 100 μL of the supernatant was diluted 4-fold and mixed thoroughly. 100 μL of this supernatant was then transferred to an ELISA plate, and the OD was measured using a multi-functional microplate reader. 652 nm .

[0046] The results are as follows Figure 6 As shown in Figure b, when the TMB concentration is between 5-20 mM, the OD increases with increasing TMB concentration. 652 nm The concentration continuously increases; when the concentration is between 20-100 mM, the OD increases with increasing TMB concentration. 652 nmThe concentration of TMB decreased continuously. This indicates that the signal was most pronounced at a concentration of 20 mM for the nanozyme; therefore, the optimal TMB concentration for this detection system is 20 mM.

[0047] 3. Amount of H2O2 used The amount of H2O2 used was set to 0, 6, 12, 18, 24, 30, 36, and 42 μL, with three replicates for each group. Each group was supplemented with 30 μL of sodium nitrite solution (1 mM), 30 μL of TMB solution (20 mM), different amounts of hydrogen peroxide solution, and 30 μL of Au-FeSAzyme nanozyme solution (0.8 mg / mL). The reaction mixture was balanced to 600 μL with acetate buffer (pH=3.5, 0.2 M) and incubated in a constant temperature shaker (37℃, 200 rpm) for 10 min, followed by centrifugation for 2 min (12000 rpm). 100 μL of the supernatant was diluted 4-fold and mixed thoroughly, then 100 μL was transferred to an ELISA plate for OD measurement using a multi-functional microplate reader. 652 nm .

[0048] The results are as follows Figure 6 As shown in Figure c, when the amount of H2O2 used is between 0-18 μL, the OD increases with the increase of H2O2 concentration. 652 nm The OD continuously increases; when the dosage is between 18-42 μL, the OD increases with the increase of H2O2 concentration. 652 nm The concentration of H2O2 continuously decreases. This indicates that the signal is most pronounced at a concentration of 18 μL. Therefore, the optimal H2O2 concentration for this detection system is determined to be 18 μL.

[0049] 4. Optimization of reaction pH Prepare NaAc-HAc buffer (0.2 M) with pH values ​​of 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, and 6. For each group, add 30 μL of sodium nitrite solution (1 mM), 30 μL of TMB solution (20 mM), 30 μL of Au-FeSAzyme nanozyme solution (0.8 mg / mL), and 18 μL of 30% H2O2 solution. Add 492 μL of buffer solution at each pH to obtain the reaction system. Incubate the reaction system in a constant temperature shaker (37℃, 200 rpm) for 10 min, then centrifuge for 2 min (12000 rpm). Dilute 100 μL of the supernatant 4-fold, mix well, and transfer 100 μL to an ELISA plate. Measure the OD using a multi-functional microplate reader. 652 nm .

[0050] The results are as follows Figure 6 As shown in Figure d, when the pH is between 2 and 3.5, the OD increases with increasing pH. 652 nm OD continuously increases; when pH is between 3.5 and 6, OD increases with increasing pH.652 nm The pH value continuously decreases. This indicates that the signal is most pronounced at a reaction pH of 3.5, therefore, pH 3.5 is the optimal pH for the reaction. Example 5

[0051] This embodiment measures and plots the standard curve of sodium nitrite solution.

[0052] Using the optimal detection conditions obtained in Example 2, sodium nitrite solutions with concentrations of 0.1, 1, 2, 5, 10, 15, and 20 mM were selected for detection. Figure 7 As shown in Figure a, the UV-Vis absorption of oxTMB in the presence of different concentrations of nitrite shows that as the nitrite concentration increases, the absorbance at 652 nm gradually decreases, and the solution color changes from blue to lighter. A standard curve is plotted with concentration on the x-axis and absorbance on the y-axis. Figure 7 (b) The regression equation is Y = −0.0246X + 3.74438, R0 2 =0.99339. Based on the concentration of nitrite solutions of different concentrations and OD... 652 nm The linear results plot shows that the method has a good linear relationship and can be used for accurate quantitative analysis of nitrite in real samples.

[0053] To verify the possibility that the superparamagnetic Au-FeSAzyme nanozyme can be recovered and reused through magnetic adsorption, a 10 mM nitrite solution was selected as the target. Figure 8 As shown, after each round of detection, the samples were recovered and reused via simple magnetic separation. A total of 3 cycles were performed. After 2 cycles, the detection efficiency was still 70%, indicating that Au-FeSAzyme nanozymes have the advantage of being recyclable. Example 6

[0054] This embodiment tests the anti-interference capability of the above-mentioned detection system.

[0055] Select common cations, anions, and organic compounds (such as Cu). 2+ Fe 2+ Mg 2+ (e.g., [missing information]) were used as interfering substances, and 10 mg / mL solutions of each interfering substance were prepared. Using the optimal detection conditions obtained in Example 4, the effects of different interfering substances and their concentrations on the absorbance at 652 nm were determined. The results are as follows: Figure 9 As shown in Figure 1, none of the interfering substances had a significant impact on the detection of nitrite, indicating that the detection system based on Au-FeSAzyme nanozyme has good catalytic selectivity for nitrite, and coexisting ions or organic substances have no or negligible interference with the system. In summary, this detection system exhibits excellent anti-interference performance. Example 7

[0056] This embodiment uses the above-described detection system to test the actual sample.

[0057] Sampling: Take one portion each of ham sausage, raw meat, and cured meat.

[0058] Sample preparation: Accurately weigh 5 g of sample, cut it into small pieces and place it in a beaker. Add 100 mL of water, sonicate for 30 min, then remove and place in a water bath at 80 ℃ or above for 2 h, stirring regularly during the process. After heating, add 5 mL of saturated mercuric chloride solution to precipitate the protein, mix thoroughly and cool. Transfer the solution to a 250 mL volumetric flask, rinse the beaker several times and combine the washings, add water to the mark, shake well, and filter through a 0.45 μm filter membrane. Collect the filtrate for later use. Divide the filtrate into four equal portions and add sodium nitrite standard solutions of different gradients to prepare test solutions with low, medium, and high spiking levels.

[0059] Using the sample solution obtained above, detection was performed according to the optimal detection conditions obtained in Example 4, and the OD was recorded. 652 nm The concentration was obtained by substituting the value into the standard curve, and the spiked recovery rate was calculated using the formula: Spiked recovery rate = (Detected concentration - Spiked concentration) / Spiked concentration × 100%. The recovery rate was between 96.32% and 108.51%, indicating that the method is accurate, reliable, and effectively applicable to the detection of nitrite in complex food matrices. The detection results for ham sausage, raw meat, cured meat, etc. are shown in Table 1.

[0060]

[0061] Example 8 This embodiment combines the method of the present invention (using the optimal detection conditions obtained in Example 4) with other detection methods. The linear range and detection limit were compared, and the results are shown in Table 2.

[0062]

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them; although the references The present invention has been described in detail with reference to preferred embodiments, and those skilled in the art should understand that it can still be applied... Modifications may be made to the specific embodiments of the present invention or equivalent substitutions may be made to some technical features without departing from the present invention. The spirit of the technical solution should be covered within the scope of the technical solution claimed in this invention.

Claims

1. A method for preparing a core-shell structured superparamagnetic gold-doped iron-based composite nanozyme based on yeast shadow, comprising the following steps: Yeast ghost, chloroauric acid solution, and ascorbic acid solution were mixed and reacted to obtain a yeast ghost@AuNPs complex containing a yeast ghost structure. The yeast ghost@AuNPs complex was then mixed evenly with ferrous ion solution, and then benzotrimethylammonium salt solution was added to react fully. The precipitate was collected by centrifugation to obtain the yeast ghost@AuNPs@Fe-MOF complex. The complex was then used to adsorb heme chloride to obtain yeast ghost@AuNPs@Fe-MOF@hemin, which was then dried and calcined to obtain the final product.

2. The preparation method according to claim 1, characterized in that: First, add chloroauric acid solution to the yeast culture and react for 1-3 hours, then add ascorbic acid solution for 15-50 minutes to obtain chloroauric acid solution.

3. The preparation method according to claim 2, characterized in that: Dry yeast was successively activated, fixed with formaldehyde, and treated with acid and alkali to obtain yeast cells.

4. The preparation method according to claim 3, characterized in that: The benzotricarboxylate solution is prepared by dissolving 1,3,5-benzotricarboxylic acid in an alkaline solution; the pH value of the benzotricarboxylate solution is 10.5-11.5, and the alkaline solution is potassium hydroxide or sodium hydroxide solution.

5. The preparation method according to claim 4, characterized in that: Ferrous ion solution is prepared by dissolving divalent ferrous salt in deionized water, and the pH value of ferrous ion solution is 2-3.

6. The preparation method according to claim 5, characterized in that: The molar ratio of chloroauric acid, 1,3,5-benzenetricarboxylic acid and divalent ferrous salt is (0.01-0.06):(1-2):(1-5).

7. The preparation method according to claim 6, characterized in that: The complex adsorbs heme chloride for 1-4 h to obtain yeast ghost@AuNPs@Fe-MOF@hemin; then it is calcined at 400-750℃ for 1-4 h to obtain the composite nanozyme.

8. A core-shell structured superparamagnetic gold-doped iron-based composite nanozyme based on yeast shadow, characterized in that: It is prepared by the preparation method according to any one of claims 1-7.

9. A method for applying the yeast shadow-based core-shell structured superparamagnetic gold-doped iron-based composite nanozyme of claim 8 in the detection of nitrite in food, comprising the following steps: After homogenizing the food sample to be tested, the supernatant was extracted and filtered. The sample supernatant, composite nanozyme aqueous solution, TMB solution, H2O2 solution and acetate buffer were mixed evenly to obtain the reaction system. After the reaction system was reacted, the absorbance at 652 nm was measured using an enzyme-linked immunosorbent assay (ELISA) reader. The measured absorbance was substituted into a pre-plotted standard curve to calculate the nitrite content in the sample to be tested.

10. The application method according to claim 9, characterized in that: The concentration of the composite nanozyme aqueous solution was 0.8 mg / mL, the amount of TMB and H2O2 used were 20 mM and 6 μL, respectively, and the pH of the reaction system was 3.5.